Evaluating the effect of a fish oil supplement on the Omega-3 Index of three professional cyclists competing in the Tour de France: a case study - Macartney, M. J.; Hesseling, M.; Ortolano, R.; McLennan, P. L.; Peoples, G. E. (Journal of Science and Cycling, 2021)
Background: Modifying the Omega-3 Index (O3I) in the elite endurance cyclist is desirable for cardiovascular and anti-inflammatory effects. This case study evaluated the effect of evidence based fish oil supplementation, providing long chain omega-3 eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), on three elite riders taking part in the Tour de France (TdF).